A T-Way test suite generation strategy for sequence based interaction testing - Mohd Zamri Zahir Ahmad (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2016)
The aim of this research is to design and evaluate a t-way test suite generation strategy, named Sequence Covering Array Test Suite Data Generation (SCATS).